Pemberdayaan Masyarakat Dusun Cetho dalam Mendokumentasikan Cagar Budaya di Kawasan Candi Cetho - Wuryani, Emy; Mediatati, Nani; Nugroho, Listyanto Aji; Purwiyastuti, Wahyu; Ambarsasi, Galuh; Jati, Dionisius Heckie Puspoko (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2024)
Cetho Temple area has many historical sites that have not been documented. Because the location and existence of the site spreads in various places and is difficult to reach by the community. RECO Community have cares about these sites. This community was built 2016 and numbered 18 people. They believe  historical sites should be cared for and protected. The wishes of the community are in line with the program of the community service from the History Education  and Civic Education Course. The purpose of the community service program is for the community to document historical sites in the Cetho Temple Area through activities they have the knowledge and skills to document cultural heritage in the area. The method is to introduce equipment for historical site documentation, exercise, practice, mentoring and evaluation. The results of the activity showed that RECO Community could use them to document historical sites.